2011
DOI: 10.1086/660811
|View full text |Cite
|
Sign up to set email alerts
|

Affect-Gating

Abstract: Neurobiological theories of affective processing suggest that different affective states can make people more sensitive to the stimulation impinging on different sensory channels. Five experiments show that consumers in a negative affective state experience enhanced sensitivity to the tactile benefits of products, whereas consumers in a positive affective state experience enhanced sensitivity to the visual benefits of products. Affect-based sensory sensitivity is a consequence of adaptations that induce mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
11
1
Order By: Relevance
“…Despite evidence that induced sadness can cause benefits (Finn & Roediger, 2011;King & Janiszewski, 2011;van Knippenberg et al, 2010; see also Jaffe, 2012 for a review), the current study did not support these findings nor did it transfer these findings to music. Emotion induction for these studies varied.…”
Section: Do Happiness and Sadness Mediate Music's Effect Of Creating contrasting
confidence: 88%
See 2 more Smart Citations
“…Despite evidence that induced sadness can cause benefits (Finn & Roediger, 2011;King & Janiszewski, 2011;van Knippenberg et al, 2010; see also Jaffe, 2012 for a review), the current study did not support these findings nor did it transfer these findings to music. Emotion induction for these studies varied.…”
Section: Do Happiness and Sadness Mediate Music's Effect Of Creating contrasting
confidence: 88%
“…In fact, it has been found that negative affect can cause an increased sensitivity to even looking at a picture of people touching each other (King & Janiszewski, 2011).…”
Section: Effects Of Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, creative ads trigger "positive emotions that transfer to intentions … even when consumer involvement is low" (Yang & Smith, 2009, p. 945). Further, when consumers are in a positive affective state, research indicates they attend more to visual information as well as the benefits of a product (King & Janiszewski, 2011). Producers of healthy food products should use these creative techniques to attract attention, transfer positive feelings to a product, and enhance the effectiveness of their advertising through visual appeal.…”
Section: Emotional Appealsmentioning
confidence: 99%
“…Touch: the mother of the senses This review identifies a parallel between disgust theory, and consumer research on perception of naturalness: touch's ability to communicate and evoke response. Despite this, there is an occularcentric disregard for touch, the mother of the senses, in consumer perception research and architectural design (Williams, 1980, p. 5;Pham et al, 2001;King & Janiszewski, 2011;Pallasmaa, 2012;Gaines et al, 2016). Consumer perception research tends to focus more on "high order" experiences of branding, and marketing, as opposed to "lower order" multi-sensory experiences (Pham et al, 2001;King & Janiszewski, 2011;Spence & Gallace, 2011).…”
Section: Naturalness Vs Typicalitymentioning
confidence: 99%